1994
DOI: 10.32685/0120-1425/bolgeol34.1.1994.354
|View full text |Cite
|
Sign up to set email alerts
|

Geología, mineralogía y química del complejo ultramáfico zonado del Alto Condoto (Cuzac)

Abstract: El platino, denominado inicialmente "platina", fue encontrado por primera vez en Colombia en la provincia del Chocó, pero la fecha exacta de su descubrimiento se desconoce a pesar de ser divulgada a partir de 1557 (FARABEE, 1921; ESPINOSA, 1980). La extracción minera de los placeres platiníferos del Chocó comenzó en 1778 y hasta 1823 fue la única fuente productora de minerales del grupo del platino (PGM) a nivel mundial, hasta que se descubrieron los aluviones platiníferos en la región de los Orales (RUSIA, 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Nevertheless, as the project concluded, reports and articles on the geological model of these deposits were published. These findings indicated that the placers resulted from the erosion of zoned ultramafic intrusions of the Alaska-Uralian type, with their mineralized source situated in the upper regions of the Condoto River (Weiser, 2002;Salinas et al, 1994;Tistl, 1994;Aiglsperger et al, 2017).…”
Section: Historical Backgroundmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, as the project concluded, reports and articles on the geological model of these deposits were published. These findings indicated that the placers resulted from the erosion of zoned ultramafic intrusions of the Alaska-Uralian type, with their mineralized source situated in the upper regions of the Condoto River (Weiser, 2002;Salinas et al, 1994;Tistl, 1994;Aiglsperger et al, 2017).…”
Section: Historical Backgroundmentioning
confidence: 99%
“…In the case of Colombia, the history, the origin of the deposit, the primary mineralizing rocks, and the culmination in the placers are known (e.g. Salazar y Adarve, 1986;Tistl, 1994;Salinas et al, 1994;Stribrny et al, 2000;Weiser, 2002;Aiglsperger et al, 2017;Redwood, 2019), but the links involving intermediate host rocks and the associated weathering processes still have many unknowns.…”
Section: Geological Origin Of Platinum In Placer Depositsmentioning
confidence: 99%
See 2 more Smart Citations